DAMPAK KEBIJAKAN TARIF IMPOR TERHADAP PASAR JAGUNG DI INDONESIA - Aulia Isnaini Putri; Bonar M Sinaga; Nia Kurniawati Hidayat; Hastuti Hastuti (Journal of Agriculture, Resource and Environmental Economics, 2014)
Maize is the second largest contributor to GDP after rice in the food crops subsector in Indonesia. The domestic maize production is unable to meet the high demand. Therefore, there is a gap or imbalance between supply and demand and maize import cannot be avoided. The implementation of ASEAN Free Trade Area has reduced and eliminated tariff barriers. The objectives of the study are to: (1) identify factors that affect the supply and demand for maize, and (2) analyze the impact of changes in maize import tariff on the supply, demand, and welfare of producers and consumers of maize in Indonesia. The study used time series data from 1986-2010. Indonesian Maize Trade model is constructed as a system of simultaneous equations and estimated method using Two Stage Least Squares (2SLS).The elimination of Indonesian maize import tariff from AFTA or non AFTA countries is leading to decreased producer surplus. Therefore, the combination of eliminating Indonesian maize import tariff from AFTA and non AFTA countries, decreasing the retail price of urea fertilizer, and increasing maize prices at the farm level can compensate the decrease of producer surplus so that the welfare can be increased(net surplus).